A review of the economics of parking. Issue 1 (March 2015) - Inci, Eren
Abstract: This paper reviews the literature on parking with an emphasis on economic issues. Parking is not just one of the most important intermediate goods in the economy; it is also a vast use of land. Many theoretical and empirical papers analyze the quantity and pricing of parking by concentrating on particular aspects of the issue. The aspects covered in this review are cruising for parking, spatial competition, (minimum and maximum) parking requirements, parking pricing and road pricing in the bottleneck model, and temporal-spatial pricing. Various forms of parking, including residential parking, shopping mall parking, and employer-provided parking, are also reviewed before identifying understudied topics that should be on the research agenda. Abstract : Highlights: This paper reviews the literature on parking with an emphasis on economic issues. Cruising for parking, spatial competition, and parking requirements are reviewed. Parking pricing and road pricing in the bottleneck model is reviewed. Temporal-spatial pricing is reviewed. Residential parking, shopping mall parking, and employer-provided parking are reviewed.